Polystyrene Backbone Polymers Consisting of Alkyl-Substituted Triazine Side Groups for Phosphorescent OLEDs - Beatrice Ch. D. Salert; Armin Wedel; Lutz Grubert; Thomas Eberle; Rémi Anémian; Hartmut Krueger (Advances in Materials Science and Engineering)
This paper describes the synthesis of new electron-transporting styrene monomers and their corresponding polystyrenes all with a 2,4,6-triphenyl-1,3,5-triazine basic structure in the side group. The monomers differ in the alkyl substitution and in the meta-/paralinkage of the triazine to the polymer backbone. The thermal and spectroscopic properties of the new electron-transporting polymers are discussed in regard to their chemical structures. Phosphorescent OLEDs were prepared using the obtained electron-transporting polymers as the emissive layer material in blend systems together with a green iridium-based emitter 13 and a small molecule as an additional cohost with wideband gap characteristics (CoH-001). The performance of the OLEDs was characterized and discussed in regard to the chemical structure of the new electron-transporting polymers.